SYI'IR TANPO WATON RECONSTRUCTION OF LOCAL CULTURE IN THE CONTEXT OF TASAWUF - Muhammad Agus Kurniawan (Pascasarjana IAIN Metro, 2021)
Syi'iran is a form of local Javanese tradition or tradition which is converted into Islamic teachings. The chanting voices of the santri reading and singing poetry and other syi'ir became the menu in the morning, afternoon, evening and night in various pesantren. Several subjects in pesantren, especially language and literature in pesantren, contribute to the existence of the image of Islam today and tomorrow. It is a